Mapping of Functional Subdomains in the atALKBH9B m6A-Demethylase Required for Its Binding to the Viral RNA and to the Coat Protein of Alfalfa Mosaic Virus - Alvarado-Marchena, Luis; Marquez-Molins, Joan; Martinez-Perez, Mireya; Aparicio, Frederic; Pallás, Vicente (Frontiers in Plant Science, 2021)
N6-methyladenosine (m6A) modification is a dynamically regulated RNA modification that impacts many cellular processes and pathways. This epitranscriptomic methylation relies on the participation of RNA methyltransferases (referred to as “writers”) and demethylases (referred to as “erasers”), respectively. We previously demonstrated that the Arabidopsis thaliana protein atALKBH9B showed m6A-demethylase activity and interacted with the coat protein (CP) of alfalfa mosaic virus (AMV) causing a profound impact in the viral infection cycle. To dissect the functional activity of atALKBH9B in AMV infection, we performed a protein-mapping analysis to identify the putative domains required for regulating this process. In this context, the mutational analysis of the protein revealed that the residues between 427-467 positions are critical for in vitro binding to the AMV RNA. atALKBH9B amino acid sequence showed intrinsically disordered regions (IDRs) located both, at the N-terminal part delimiting the internal AlkB-like domain and at the C-terminal part. We identified an RNA binding domain containing a RGxxxRGG motif which overlapps with the C-terminal IDR. Moreover, bimolecular fluorescent experiments allowed us to determine that residues located between 387-427 are critical for the interaction with the AMV CP, which should be critical for modulating the viral infection process. Finally, we observed that atALKBH9B deletions either of the N-terminal 20 residues or the C-terminal last 40 amino acids impede its accumulation in siRNA bodies. The involvement of the regions responsible for RNA and viral CP binding as well as those required for its localization in stress granules in the viral cycle is discussed.